Duolingo as A Mobile-Assisted Language Learning: A New Supplementary of Learning Basic English Reading for EFL Students - Hegar Hakimantieq; Didi Suherdi; Wawan Gunawan (Universitas Pahlawan Tuanku Tambusai, 2022)
It is undeniable, that the world of education is affected by technological advances this study discusses the process of using an already developed language learning online software, Duolingo, to supplement learning basic English reading for senior high school EFL students. A mixed approach of qualitative and quantitative data collection is followed in this research paper. The learners that consist of 10 students had used the software online for about 30 days, either on their smartphone or on their personal computer. Based on the questionnaire result survey, the students usually enjoy the learning process because of several factors; such as easiness of its accessibility, its game-based aspect, could discussion of the problem with other players, and interactive features and illustrations. The result of the assessment also conducted by http://efset.org shows that the Duolingo online language learning platform could help the students achieve more from the expected result of the basic English reading target needs to be based on the CEFR assessment standard result, in another fun and also still on the appropriate way for teaching English, especially in English reading. Based on the result, it is essential to consider that using online applications could be one of the appropriate ways and beneficial ways for students to achieve better results in learning, especially in learning the English language.